2017
DOI: 10.3389/fnagi.2016.00337
|View full text |Cite
|
Sign up to set email alerts
|

68 and FX2149 Attenuate Mutant LRRK2-R1441C-Induced Neural Transport Impairment

Abstract: Leucine-rich repeat kinase 2 is a large protein with implications in genetic and sporadic causes of Parkinson's disease. The physiological functions of LRRK2 are largely unknown. In this report, we investigated whether LRRK2 alters neural transport using live-cell imaging techniques and human neuroblastoma SH-SY5Y cells. Our results demonstrated that expression of the PD-linked mutant, LRRK2-R1441C, induced mitochondrial, and lysosomal transport defects in neurites of SH-SY5Y cells. Most importantly, recently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 59 publications
(101 reference statements)
0
27
0
Order By: Relevance
“…Recent studies have described the identification of several LRRK2 GTP-binding inhibitors able to attenuate LRRK2 toxicity, and able to rescue vesicular transport deficits associated with impaired neurite outgrowth ( 39–41 ). Both compound 68 and compound 70 significantly reduced LRRK2 GTP binding in vitro ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have described the identification of several LRRK2 GTP-binding inhibitors able to attenuate LRRK2 toxicity, and able to rescue vesicular transport deficits associated with impaired neurite outgrowth ( 39–41 ). Both compound 68 and compound 70 significantly reduced LRRK2 GTP binding in vitro ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Various independent studies have reported that LRRK2 interacts with MTs, even though a preferential association with dynamic versus stable MTs has remained unclear ( 31 , 33–35 ). Whilst the presence of LRRK2 in growth cones has been taken to indicate that it may preferentially interact with dynamic MTs ( 39 ), such localization may be contributed to by additional factors. Furthermore, the previously reported alternating nature between the presence of pathogenic LRRK2 and acetylated α-tubulin staining has been taken as evidence that it interacts with dynamic MTs ( 35 ), but our data suggest this to be an unlikely interpretation for several reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we conclude that pathogenic LRRK2 antagonizes not only the TRIM32-induced miRNA activity but also neuronal differentiation. Finally, since reduced neurite complexity is a well-known characteristic of in vitro cell culture models for PD [ 27 ], we also analyzed this feature. In the here used assay, expression of TRIM32 had no effect on neurite number, branching, or length.…”
Section: Resultsmentioning
confidence: 99%
“…Putative pharmacological inhibitors of LRRK2 GTPbinding have also been reported (i.e. FX2149) although their selectivity profiles and mode of action are poorly defined (53,54).…”
Section: G2019s Mutation In Vivomentioning
confidence: 99%